2011
DOI: 10.1007/s11064-010-0380-3
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Alterations of Sphingolipid Metabolism in Lysosomal Storage Diseases

Abstract: In several neurodegenerative diseases, sphingolipid metabolism is deeply deregulated, leading to the expression of abnormal membrane sphingolipid patterns and altered plasma membrane organization. In this paper, we review the potential importance of these alterations to the pathogenesis of these diseases and focus the reader's attention on some secondary alterations of sphingolipid metabolism that have been sporadically reported in the literature. Moreover, we present a detailed analysis of the lipid compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 130 publications
(109 reference statements)
1
25
0
1
Order By: Relevance
“…This finding is surprising, as MCD is known to induce steatosis by preventing hepatic phosphatidylcholine (PC) synthesis, which in turn, impairs VLDL secretion to the circulation resulting in liver TG loading and subsequent fatty liver. Previous findings reported that ASMase deficiency results in higher PC levels both in brain and liver compared to ASMase +/+ tissues [32]. In line with these findings, we observed that ASMase −/− mice fed MCD exhibited higher liver PC levels than ASMase +/+ mice, suggesting that ASMase deficiency spares PC to prevent VLDL accumulation in the absence of methionine and choline.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is surprising, as MCD is known to induce steatosis by preventing hepatic phosphatidylcholine (PC) synthesis, which in turn, impairs VLDL secretion to the circulation resulting in liver TG loading and subsequent fatty liver. Previous findings reported that ASMase deficiency results in higher PC levels both in brain and liver compared to ASMase +/+ tissues [32]. In line with these findings, we observed that ASMase −/− mice fed MCD exhibited higher liver PC levels than ASMase +/+ mice, suggesting that ASMase deficiency spares PC to prevent VLDL accumulation in the absence of methionine and choline.…”
Section: Discussionsupporting
confidence: 91%
“…The subsequent formation of foam cells and the massive lysosomal proliferation are thought to contribute to the known hepatomegaly in NPA disease [45]. These changes in the liver are variable as they are age-dependent, being more prominent in older mice (>12–14 weeks of age) [46]. …”
Section: Discussionmentioning
confidence: 99%
“…The generation of ASMase À/À mice has been a useful tool to study its role in cellular stress, infection, and apoptosis [98][99][100][101]. ASMase deficiency models Niemann-Pick type A disease, a lysosomal storage disease characterized by the accumulation of SM, cholesterol, and glycosphingolipids in lysosomes of affected organs, particularly brain and liver [102,101]. ASMase is expressed in almost every cell type and is located mainly within the endosomal/lysosomal compartment, although it has also been found in specific microdomains in the plasma membrane functioning as a signalling platform for cell surface receptors (e.g.…”
Section: Asmase Promotes Hepatocellular Apoptosis Liver Fibrosis Andmentioning
confidence: 99%
“…Although the specific pathway, contributing to the described increased hepatic ceramide content in LCCTa À/À mice, remains to be determined, an attractive possibility would be the activation of ASMase, establishing a link between low PC and ASMase activation. Accordingly, ASMase À/À mice exhibit increased PC levels in the liver and brain [102], which contribute to the protection of ASMase À/À mice against MCD-induced hepatic steatosis [17]. Although further work is needed to characterize the functional relationship between ASMase and PC, it appears that PC reduction and ASMase activation engage in a vicious cycle of potential significance in steatohepatitis.…”
Section: Asmase Regulates Pc Homeostasismentioning
confidence: 99%